The Development of Kinesthetic Skills in the Lembu Dance Extracurricular Program at Elementary School - Prabawati, Bunga Anggun; Nurharini, Atip (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
This study aims to analyze the contribution of Lembu Creation Dance in extracurricular dance activities at SD Negeri Gondangrawe to the development of students' kinesthetic intelligence. Lembu Creation Dance is a modern dance art rooted in Indonesian culture, depicting the symbolism of the ox as an animal with significant historical and spiritual value. This study uses a qualitative approach with a descriptive method based on case studies. Data were obtained through observation, interviews, and documentation of 15 students who participated in extracurricular dance activities. The results showed that Lembu Creation Dance significantly increased students' kinesthetic intelligence through structured exercises involving body coordination, balance, flexibility, and understanding of symbolic meaning in dance movements. In addition to physical benefits, this activity also contributes to psychological aspects, such as increased self-confidence, courage to appear in public, and social skills. Participation in dance activities also shapes students' character, such as discipline, patience, and perseverance. However, several obstacles affect the effectiveness of this program, including limited facilities, short practice time, and variations in students' interests and abilities. To optimize this program, it is necessary to provide adequate facilities, flexible schedules, and innovative learning approaches involving technology. This study confirms that Lembu Creative Dance is not only a medium for preserving local culture but also a holistic educational tool to develop the physical, mental, and emotional potential of students as a whole